2022
DOI: 10.3390/ijms23158670
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combining Biofactors on Bioenergetic Parameters, Aβ Levels and Survival in Alzheimer Model Organisms

Abstract: Increased amyloid beta (Aβ) levels and mitochondrial dysfunction (MD) in the human brain characterize Alzheimer disease (AD). Folic acid, magnesium and vitamin B6 are essential micro-nutrients that may provide neuroprotection. Bioenergetic parameters and amyloid precursor protein (APP) processing products were investigated in vitro in human neuroblastoma SH-SY5Y-APP695 cells, expressing neuronal APP, and in vivo, in the invertebrate Caenorhabditis elegans (CL2006 & GMC101) expressing muscular APP. Model or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 92 publications
0
20
0
Order By: Relevance
“…However, our cell model is not one in which there is a deficit of Mg and Fol. Furthermore, in our studies, no increase in ATP levels was observed by the single administration of MgOr and Fol [43]. In contrast, the combination KCC increased ATP levels [source].…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…However, our cell model is not one in which there is a deficit of Mg and Fol. Furthermore, in our studies, no increase in ATP levels was observed by the single administration of MgOr and Fol [43]. In contrast, the combination KCC increased ATP levels [source].…”
Section: Discussionmentioning
confidence: 51%
“…Reduction of Nrf-2 results in decreased MMP, decreased ATP levels and impaired mitochondrial respiration [58]. A reduction of Aβ levels by MgOr and Fol, would be also a possible explanation [43]. This could reduce the impairment of complexes by Aβ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have been carried out to identify dysfunctions affecting the quality control mechanisms of mitochondria (for refs, see [82]), giving clear evidence that all involved steps are impaired in AD pathogenesis (for refs, see [83]).…”
Section: The Mitochondrion: Its Dysfunctions In Admentioning
confidence: 99%
“…Many studies have been carried out to identify dysfunctions affecting the quality control mechanisms of mitochondria (for refs, see [82]), giving clear evidence that all involved steps are impaired in AD pathogenesis (for refs, see [83]). Although there are different localizations of toxic proteins, i.e., intra-vs. extracellular protein for Tau and Aβ, respectively, both can influence the mitochondrial function at different levels (transport, morphology and mitochondrial bioenergetics).…”
Section: The Mitochondrion: Its Dysfunctions In Admentioning
confidence: 99%